Hranice práce - Rychlikova, Apolena; Procházková, Jitka; Klusák, Vít; Remunda, Filip; Šejnoha, Ondřej; Kubica, Petr; Krutská - Vrbová, Kateřina; Rychlíková, Apolena; Uhlová, Saša; Šípek, Jan; Pecháčková, Marika; Frkal, Tomáš; et al. (Czech Republic : Institute of Documentary Film, 2017)
Journalist Saša Uhlová sets out on a quest to explore the conditions of the worst-paid jobs in the Czech Republic. She applies to work in a hospital washroom, at a poultry-processing plant, behind a cash register, and at a waste sorting facility. Her experience formed the basis for a very personal series of reports about people working invisible jobs under shocking conditions that was published on the A2larm.cz website. Apolena Rychlíková’s documentary uses candid camera footage taken at these work places and combines them with everyday scenes from Uhlová’s life accompanied by her read commentary.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films